CLINICAL EVALUATION OF TRANSCUTANEOUS CARBON DIOXIDE MONITOR (TOSCA) IN PATIENTS WITH MOTOR NEURONE DISEASE. (29th November 2012) - Rafiq, M; Proctor, AR; McDermott, CJ; Shaw, P
Abstract : Background: Motor Neurone Disease (MND) causes progressive disability and neuromuscular respiratory failure is the commonest cause of death. Detection of respiratory failure (PCO2>6 kPa by definition) and treatment with non-invasive ventilation, can improve quality of life and survival. Recording carbon dioxide level transcutaneously with a TOSCA 500 monitor (Linde Medical Sensors), offers a non-invasive and simple method to screen for respiratory failure in patients with MND. The aim of this study is to validate the accuracy of the TOSCA monitor. Methods: This is a prospective study of 40 consecutive patients with MND. The carbon dioxide level in each patient was determined by both transcutaneous monitoring and by an arterialised ear lobe capillary blood sample. The carbon dioxide levels obtained by these two methods were compared by a modified Bland-Altman analysis. Results: The mean difference between arterialised and transcutaneous readings was 0.083 kPa (SD 0.318). The Bland-Altman limits of agreement ranged from −0.553 to 0.719. The difference was<0.5 kPa in 90% of the subjects. Four of the forty measurements had a difference of>0.5 kPa with the maximum recorded difference of 0.95 kPa. Conclusions: Non-invasive carbon dioxide monitoring using a TOSCA monitor is a useful clinical tool in neurology practice. The users should be aware of the possibility of occasional inaccurate readings. A clinically unexpected or incompatible reading should be verified with a blood gas analysis, especially when a decision to provide ventilatory support is required.